Elseworlds and Uchronias: Whatever Happened to the Man of Tomorrow? A Decolonial Study (Letras, 2025)
A comparative analysis is proposed about the DC comics representations (hereinafter, DC), although emphasizing the Superman’s figure. At this point of convergence of readings, the objective is to shed light on the practices of power from the decolonial studies. The main sources are the comicbook Superman Red Son by Mark Millar and the novel Kryptonita by the Argentinian writer Leonardo Oyola. The main question is whatever happened to the Man of the Tomorrow? Different representations of this Mass culture myth are contrasted from different points of view: from the Susan Buck-Morss’ perspective of failed utopias or from the Group Modernidad/Colonialidad, and the approach of epistemologías del Sur.
Keywords: Elseworlds; Uchronia; Utopia; Superman; Decolonial